Storytelling in Destination Marketing - Keskitalo, Riikka Annika (2020)
The aim of this thesis was to find ways to enhance social media marketing of a nature destination. True Lapland is a destination brand of Enontekiö, which is managed by a development department of the Municipality. Social media marketing is a relatively cost-effective marketing channel with remarkable reach, but only if the content is engaging. Storytelling is an ancient way for humans to entertain and deliver information, and stories are still powerful to catch our attention. This thesis finds ways to bring some storytelling techniques to the era of social media. Travel industry is one of the biggest markets in the world, also the most significant branch in Enontekiö. As the industry produces experiences, using storytelling in destination marketing was hypothetically profitable. Destination marketing and the industry’s other characteristics are shortly introduced by evaluating secondary data, academic and contemporary publications. Information about the destination bases on the interview and the workshop with True Lapland’s participants. Information is accompanied by the author’s work experience with the brand and own experience while living in the area. Storytelling in business and different techniques were researched by investigating contemporary publications on the cause. Social media is a great platform for storytelling, as it fulfills people’s social needs and will to tell and hear stories. Results show that stories that resonate with the audience’s values and world view deliver the message effectively. In addition, the message should remain simple and easy to understand. Stories in social media should follow AIDA-model to trigger wanted actions. Storytelling techniques will be applied in True Lapland social media marketing to enhance reaching marketing objectives.